Ureteral Reimplantation with Psoas Bladder Hitch in Adults: A Contemporary Series with Long-Term Followup - Francesca Manassero; Andrea Mogorovich; Girolamo Fiorini; Giuseppe Di Paola; Maurizio De Maria; Cesare Selli (The Scientific World Journal)
We retrospectively evaluated our experience with ureteral reimplantation and psoas bladder hitch to restore urinary tract continuity in patients with lower ureteral defects, since long-term data on the outcomes of this procedure have been relatively scarce in the last two decades. The procedure was performed in 24 patients (7 male, 17 female) with a mean age of 54.6 years. The mean ureteral defect length was 4.8 cm (range 3–10), the ureterovesical anastomosis was performed with simplified split-cuff technique in 18 patients, submucosal tunnel in 2, and direct anastomosis without antireflux technique in 2. Mean followup was 53 months (range 12–125), and there were no reinterventions. Postoperative renal imaging was normal in 22 cases (91.6%) and revealed decreased kidney size in 2, 3 patients presented intermittent flank pain, and 5 had sporadic episodes of lower tract UTI but no one pyelonephritis. Psoas hitch ureteral reimplantation can be successfully used for bridging defects of the lower ureter up to 10 cm in length in difficult clinical situations. It is relatively simple to perform, compared to other procedures of ureteral reconstruction, and it provides adequate protection of the upper urinary tract.